A Decade of Change: Roper v. Simmons, Defending Childhood, and Juvenile Justice Policy. (February 2019) - Benekos, Peter J.; Merlo, Alida V.
In the last decade, juvenile justice has emerged with more compassion and child-focused policies. During this time, crime decreased, successful strategies for prevention and intervention were identified, neuroscience examined the wiring of the adolescent brain, and the Attorney General established a federal mandate to recognize and respond to children exposed to violence (CEV). In this context, the authors identify two developments that contributed to the ongoing iterations of juvenile justice: Supreme Court decisions that restrict excessive juvenile punishments and policies that recognize the consequences of childhood trauma and the importance of relevant treatment. The Supreme Court rationale in Roper v. Simmons, Graham v. Florida, Miller v. Alabama, and Montgomery v. Louisiana was instrumental in underscoring that youth are different from adults and therefore require different sentencing. The second development was a broader understanding of the scope and consequences of childhood trauma which renewed support to identify and care for youth exposed to violence. The authors review the Court's rationale in moving policy away from harsh punishment and retribution, the evidence-based support for trauma-informed treatment of youth, and the limits of Court decisions and policy changes in reforming juvenile justice.